Multifunctional Biomimetic Nanovaccines Based on Photothermal and Weak-Immunostimulatory Nanoparticulate Cores for the Immunotherapy of Solid Tumors - Li Jiachen; Huang Di; Cheng Ruoyu; Figueiredo Patrícia; Fontana Flavia; Correia Alexandra; Wang Shiqi; Liu Zehua; Kemell Marianna; Torrieri Giulia; Mäkilä Ermei M.; Salonen Jarno J.; et al. (Wiley, 2022)
An alternative strategy of choosing photothermal and weak-immunostimulatory porous silicon@Au nanocomposites as particulate cores to prepare a biomimetic nanovaccine is reported to improve its biosafety and immunotherapeutic efficacy for solid tumors. A quantitative analysis method is used to calculate the loading amount of cancer cell membranes onto porous silicon@Au nanocomposites. Assisted with foreign-body responses, these exogenous nanoparticulate cores with weak immunostimulatory effect can still efficiently deliver cancer cell membranes into dendritic cells to activate them and the downstream antitumor immunity, resulting in no occurrence of solid tumors and the survival of all immunized mice during 55 day observation. In addition, this nanovaccine, as a photothermal therapeutic agent, synergized with additional immunotherapies can significantly inhibit the growth and metastasis of established solid tumors, via the initiation of the antitumor immune responses in the body and the reversion of their immunosuppressive microenvironments. Considering the versatile surface engineering of porous silicon nanoparticles, the strategy developed here is beneficial to construct multifunctional nanovaccines with better biosafety and more diagnosis or therapeutic modalities against the occurrence, recurrence, or metastasis of solid tumors in future clinical practice.